Efektifitas Pemberian Non Nutritive Sucking Terhadap Respon Nyeri Neonatus Pada Pemberian Imunisasi Hb0 Diruang Perinatologi Rs X Husada Malang: Effect Of Non-Nutritive Sucking Administration On Neonate Pain Response In Hb0 Immunization In The Perinatology Room Of X Husada Hospital Malang - Nengrum, Lilis Sulistiya; Istiqomah, Mahmudatul (Borneo Journal of Medical Laboratory Technology, 2024)
Neonatal pain response is an unpleasant experience due to subjective damage to body tissues which can be assessed by facial expressions, body movements, crying and resting using a pain scale. This study aims to determine the effect of Non-Nutritive Sucking on neonatal pain response to HB0 immunization at Wava Husada Malang Hospital. This study used a quasi-experimental post test only control group design. The sample of this study were neonates with a maximum age of less than 24 hours as many as 28 respondents. Using Accidental sampling technique. The independent variable is Non-Nutritive Sucking and the dependent variable is neonatal pain response. Data collection is by taking samples according to the inclusion criteria which are divided into the intervention group and the control group, the data ratio scale. Data analysis used the Mann-Whitney U test (alpha 0.05). The mean response to pain in the control group was higher than the average response to pain in the intervention group. The results of the Mann-Whitney U statistical test obtained a value of Z = -3.90 with a p value = 0.000 which indicated that there was a significant difference in neonatal pain responses in infants during HB0 immunization between the intervention group and the control group.